Transvaginal echo-guided drainage of an ovarian tubo abscess in the gynecological emergency of Meulan Les Mureaux about a case and review of the literature - Kakou, Charles; Kasse, Raoul; Bakar, Joseph (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Tubo-ovarian abscesses (TOA) complicate 10 to 35% of upper genital infections (UGI). The diagnosis is based on a clinical-bio-radiological tripod. Treatment requires surgery or interventional imaging. We report a case of TOA drained by transvaginal ultrasound guidance in the gynecological emergency room of the Meulan-Les Mureaux intercommunal hospital center. This treatment was associated with probabilistic antibiotic triage therapy. The evolution was marked by a regression of the clinical symptoms and by a regression of the biological markers of inflammation on the 3rd day post drainage. This approach, less invasive than laparoscopy, should be favored in the event of comorbidity or unavailability of endoscopy. It can be an alternative to classic laparotomy in the absence of any contraindication.